Mental health symptoms among men and women Australian professional football (soccer) players: a survey-based cross-sectional study - Mifsud, D.; van Rensburg, D. C. J.; Busch, B.; Mankowska, R.; Taylor, B.; Kerkhoffs, G.; Gouttebarge, V. (BMC Sports Science, Medicine and Rehabilitation, 2026)
Objectives The primary aim of this study was to determine the prevalence of mental health symptoms among men and women Australian professional footballers, drawing comparisons with prevalence rates from 2020. A secondary aim was to assess whether mental health symptoms among men and women Australian professional footballers were associated with recent injury and/or psychological resilience.